The description procedure - Migliore, Tiziana (E|C, 2020)
It is difficult to tackle the theme of the "semiotic method" without asking first a problem, which is that of the positioning of semiotics among the disciplines. What is the state of health of semiotics in Italy, where Eco did he founded and instituted it as a discipline?